2015
DOI: 10.3892/mmr.2015.4609
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-145 inhibits the malignant phenotypes of gastric carcinoma cells via downregulation of fascin 1 expression

Abstract: MicroRNA (miR)‑145 has been demonstrated to act as a tumor suppressor, and deregulation of fascin 1 (FSCN1) has been observed in several types of human malignancy, including gastric carcinoma. However, the molecular mechanism underlying the function of miR‑145, specifically its targets in gastric carcinoma have yet to be fully elucidated. In the present study, downregulation of miR‑145 and upregulation of FSCN1 was identified in gastric carcinoma cell lines, compared with normal gastric mucosal epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Previous studies showed that miR-138 is downregulated in OSCCs [ 19 , 20 ] and in silico target analysis revealed a conserved miR-138-binding site within 3' UTR of fascin mRNA ( www.targetscan.org ). Similarly, previous studies revealed that miR-145 regulates fascin expression in several different tumors [ 21 , 22 ]. miR-138 showed a significant and inverse correlation with fascin levels (rho=-0.68 and p=0.04), whereas no correlation was observed for miR-145 (Figure 11A ).…”
Section: Resultssupporting
confidence: 62%
“…Previous studies showed that miR-138 is downregulated in OSCCs [ 19 , 20 ] and in silico target analysis revealed a conserved miR-138-binding site within 3' UTR of fascin mRNA ( www.targetscan.org ). Similarly, previous studies revealed that miR-145 regulates fascin expression in several different tumors [ 21 , 22 ]. miR-138 showed a significant and inverse correlation with fascin levels (rho=-0.68 and p=0.04), whereas no correlation was observed for miR-145 (Figure 11A ).…”
Section: Resultssupporting
confidence: 62%
“…Several studies have shown that the interaction of miR-145 and miR-133 with FSCN1 is crucial to inhibit migration and invasion of cancer cells. 127–129 To our knowledge, it has not yet been associated with atherosclerosis and cardiovascular diseases. Reduction of miR-133a expression was associated with lower IGF1R levels and suppression of VSMC growth through modulation of the Akt/FOXO3a pathway.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous research showing that miR‐181b was involved in transforming growth factor beta‐induced epithelial‐to‐mesenchymal transition and GC metastasis (Zhou et al ., ). Considering protective factors, we noted that miR‐145 could inhibit the malignant phenotypes and suppress metastasis of GC via different molecular mechanisms (Gao et al ., ; Lei et al ., ; Tong et al ., ; Xing et al ., ; Xue et al ., ; Zheng et al ., ). In another study, miR‐7‐3 was confirmed to be an independent prognostic indicator for stomach adenocarcinoma (Huo, ).…”
Section: Discussionmentioning
confidence: 99%